Development of Knowledge management system to Support Knowledge Sharing Among Lecturers: Case Study at STMIK Antar Bangsa : Pengembangan sistem manajemen Pengetahuan untuk Mendukung Berbagi Pengetahuan Antar Dosen: Studi Kasus di STMIK Antar Bangsa - Esthi Adityarini (Universitas Singaperbangsa Karawang, 2021)
Knowledge Management is the process of creating, sharing, using, and managing knowledge andinformation from an organization. A good organization can certainly manage information properly andcorrectly. On the STMIK Antar Bangsa campus there are obstacles regarding tacit and explicitknowledge which are only stored in the individual from various activities such as seminars, workshops,comparative studies and other activities that are followed but there is no place to accommodate theknowledge they have to be able to be disseminated to other lecturers . For this reason, to solve theseproblems, a knowledge management system is needed to manage the web-based lecturer knowledgesharing. This research method uses the Amrit Tiwana model framework with some adjustments and thesystem testing technique uses User Acceptance Test (UAT). The results of the analysis will be obtaineda Prototype of knowledge management system that is suitable for supporting knowledge sharingbetween lecturers at STMIK Antar Bangsa.